2002
DOI: 10.1161/01.cir.0000038303.84249.4a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atorvastatin on High-Density Lipoprotein Apolipoprotein A-I Production and Clearance in the New Zealand White Rabbit

Abstract: Background-HMG-CoA reductase inhibitors reduce the incidence of cardiovascular disease predominantly by their LDL-lowering effect. Recently, there has been great interest in the pleiotropic effects of statins, which appear to differ among the various agents in this class. Unlike other statins, atorvastatin exhibits a decline in its HDL-raising effect at higher doses in humans. Whether atorvastatin-mediated alterations in HDL turnover in vivo contribute to this effect has not previously been investigated. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…With respect to HDL, atorvastatin showed a significant decrease in its level compared with the cholesterol-fed group. This was in agreement with the study conducted by Rashid et al [24] who found that atorvastatin, in contrast to some other statins, appears to lose its HDLraising effect at high therapeutic doses (40-80 mg). This effect is attributable to the more rapid clearance of HDL apo A-1 (the major protein component of HDL) occurring in the presence of smaller increase in apoA-1 production.…”
Section: Discussionsupporting
confidence: 93%
“…With respect to HDL, atorvastatin showed a significant decrease in its level compared with the cholesterol-fed group. This was in agreement with the study conducted by Rashid et al [24] who found that atorvastatin, in contrast to some other statins, appears to lose its HDLraising effect at high therapeutic doses (40-80 mg). This effect is attributable to the more rapid clearance of HDL apo A-1 (the major protein component of HDL) occurring in the presence of smaller increase in apoA-1 production.…”
Section: Discussionsupporting
confidence: 93%
“…For example, 3-hydroxy-3-methylglutaryl-CoA reductase inhibitors, or "statins," used primarily to decrease LDL-C levels, have been found in some in vitro studies to increase apoA-I synthesis and to have minor inhibitory effects on CETP and hepatic lipase, factors that could affect HDL metabolism (76,77). Clinically, statins generally increase plasma HDL-C concentrations by between 5% and 10%, with minor differences in HDL-increasing effects reported between various statins.…”
Section: Hdl Kinetics In Humans Administered Pharmacotherapiesmentioning
confidence: 99%
“…Similarly, although some studies suggested a beneficial effect of atorvastatin on apoAI production (Schaefer et al, 1999), enhancing transcription of apoAI mRNA by activating peroxisome proliferator-activated receptor-␣ (Martin et al, 2001), others suggested a dose-dependent effect on apoAI concentration (increase under low dose and decrease under higher dose) (Wierzbicki and Mikhailidis, 2002). No effect on apoAI kinetics (Watts et al, 2003) and concentration (Asztalos et al, 2002), or even a decrease in apoAI concentration, associated with an enhanced catabolic rate in an animal model (Rashid et al, 2002), has been reported.…”
mentioning
confidence: 99%